2011
DOI: 10.3892/ijo.2011.1198
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic activity of cranberry proanthocyanidins and cytotoxic properties in ovarian cancer cells

Abstract: Abstract. Cranberry extracts may provide beneficial health effects in the treatment of various diseases, including cancer. However, the underlying molecular mechanisms of antineoplastic properties are not understood. We report the effect of a proanthocyanidin (PAC)-rich isolate from cranberry (PAC-1) as a therapeutic agent with dual activity to target both ovarian cancer viability and angiogenesis in vitro. PAC-1 treatment of chemotherapy-resistant SKOV-3 cells blocked cell cycle progression through the G 2 /M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 50 publications
2
58
0
2
Order By: Relevance
“…Thus, cranberry proanthocyanidins modulate cell death via inactivation of the PI3K/AKT/mTOR signaling axis, but may be dependent on available cell death machinery. A decrease in signaling through the AKT pathway is also observed in SKOV-3 ovarian cancer cells treated with cranberry proanthocyanidins [49].…”
Section: Cranberry Derived Extracts and Constituents Induce Cell Deatmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, cranberry proanthocyanidins modulate cell death via inactivation of the PI3K/AKT/mTOR signaling axis, but may be dependent on available cell death machinery. A decrease in signaling through the AKT pathway is also observed in SKOV-3 ovarian cancer cells treated with cranberry proanthocyanidins [49].…”
Section: Cranberry Derived Extracts and Constituents Induce Cell Deatmentioning
confidence: 85%
“…LS-513 colon cancer cells are particularly susceptible to viability reductions following exposure to a total polyphenolic fraction (3.8-92.9 µg/mL) and anthocyanins (4.3-75.5 µg/mL) when compared to a cranberry juice extract (38.11-113.0 µg/mL) [32]. Cranberry proanthocyanidins also decrease the viability of neuroblastoma, esophageal adenocarcinoma and ovarian cancer cells [40,41,44,45,48,49]. All four neuroblastoma cancer cell lines (IMR-32, SH-Sy5Y, SK-N-SH and SMS-KCNR) show significant reductions in viability when treated with 12.5-25.0 µg/mL of cranberry proanthocyanidins [44,45].…”
Section: Cjementioning
confidence: 99%
“…All four neuroblastoma cancer cell lines (IMR-32, SH-Sy5Y, SK-N-SH and SMS-KCNR) show significant reductions in viability when treated with 12.5-25.0 µg/mL of cranberry proanthocyanidins [44,45]. In comparison, a significant reduction in viability of esophageal adenocarcinoma and ovarian cancer cells is observed with 25.0-50.0 µg/mL and 50.0-200.0 µg/mL cranberry proanthocyanidins, respectively [40,41,45,48,49]. Reductions in viability of glioblastoma and melanoma cancer cell lines occur following treatment with a flavonoid rich extract, with the GI 50 for U87 glioblastoma cells about half of the GI 50 for SK-MEL5 melanoma cells after a 96h treatment [28].…”
Section: Cjementioning
confidence: 99%
“…Conversely, there are reasons to suspect that cranberry therapy may not be safe for the fetus. Cranberries contain many polyphenolic compounds with proven anti-angiogenic activity on tumor angiogenesis: phenolic acids and flavonoids, including catechins and catechin polymers which are strongly antiangiogenic procyanidins (Roy et al 2002, Kiran et al 2008, Kanjoormana and Kuttan 2010, Kim et al 2012. Moreover, it has been shown that triterpenoid ursolic acid, which is present in cranberries, inhibits not only tumor angiogenesis, but also inhibits embryonal angiogenesis in experiments on chicken embryos (Sohn et al 1995).…”
Section: Introductionmentioning
confidence: 99%